WAYS TO ORGANIZE LABOR AUTONOMY IN PHYSICAL EDUCATION AND SPORTS AND REDUCE INJURIES - Jumanova Makhsudakhan Sattarovna; Latibov Shokhrukhbek Makhamatyusup o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses ways to improve occupational safety in sports and the educational institution’s gymnasium, outdoor sports field, as well as sports equipment and any additional equipment used in the classroom to meet safety standards and improve working conditions.